Bioreactors for tendon tissue engineering: challenging mechanical demands towards tendon regeneration - Gonçalves, A I (2018)
Tendon tissues have very important load-bearing and load-transfer functions, and are also very prone to injuries that can dramatically affect patientâ s quality of life and which are difficult to manage successfully with current available therapies. Regenerative approaches following tendon tissue engineering (TTE) principles have sought to augment the injured tendon with stem cells, scaffolds and mechanical stimulus to improve natural healing response. In fact, combinatorial tenogenic cues may involve adequate topographical, biochemical and mechanical signals for recapitulating native cellular microenvironment and thus promote regeneration. Hence, for the successful implementation of TTE therapies, all aspects of tendon function and requirements should be taken into account in the in vitro maturation of constructs prior implantation. In this sense, bioreactor systems represent attractive tools to provide biomechanical signaling to cells-laden constructs under closely monitored and tightly controlled environments. This chapter discusses specific roles of biomechanical stimulation in tendons and the most frequently used bioreactor systems in tendon tissue engineering field.